Dendrophthoe pentandra Leaves Extract Promotes Apoptotic Effects of Doxorubicin in Human Breast Cancer Cell via Modulation of Intracellular Calcium and Survivin - Agustina Tri Endharti & , Tri Esti Wahyuningtyas, Hardini, Kusworini Handono, Edi Widjajanto, Sofy Permana (Journal of Applied Pharmaceutical Science, 2018)
Dendrophthoe pentandra is a parasitic plant that has anticancer activity. The leaf of Dendrophthoe pentandra traditionally has been used for anticancer agents. The aim of this study was to investigate whether the combination of Dendrophthoe pentandra leaves extract (DPE) and doxorubicin reduces intracellular calcium concentration [iCa2+] and survivin levels while increasing the number of apoptotic cells in MCF-7 breast cancer cell lines. MCF-7 cells were cultured and divided into six groups: group 1 is a negative control (without DPE nor doxorubicin); group 2 was treated with doxorubicin alone; groups 3-5 were treated with DPE in doses of either 12.5, 25, or 50 μg/ml immediately after doxorubicin treatment, and group 6 was treated with 50 μg/ml of DPE alone. After 24 hours of treatment, we assessed the concentration of iCa2+, survivin levels and the number of apoptotic cells by flow cytometry. The combination of doxorubicin and DPE significantly reduced the percentage of survivin (P < 0.05) and iCa2+ concentration (P < 0.05); whereas the number of apoptotic cells increased significantly (P < 0.05). Therefore, we concluded that the anti-cancer effect of doxorubicin can be enhanced when combined with DPE.
Keywords: Apoptosis, intracellular calcium, Dendrophthoe pentandra extract, doxorubicin, survivin.